Evaluation of feedback methods for improved detection of hindlimb lameness in horses among riding instructors and trainers - Leclercq, Anna; Byström, Anna; Söderlind, Maja; Persson, Elisabeth; Rhodin, Marie; Engell, Maria Terese; Hernlund, Elin (Frontiers in Veterinary Science, 2022)
Lameness, a well-known issue in sport horses, impedes performance and impairs welfare. Early detection of lameness is essential for horses to receive needed treatment, but detection of hindlimb lameness is challenging. Riding instructors and trainers observe horses in motion in their daily work and could contribute to more efficient lameness detection. In this cross-sectional and prospective study, we evaluated the ability of riding instructors and trainers to assess hindlimb lameness. We also evaluated different feedback methods for improved lameness detection. For the cross-sectional part, n=64 riding instructors and trainers of varying level and n=23 high-level trainers were shown 13 videos of trotting horses, lameness degree: 0-3.5 (test 1) and tasked with classifying the horses as sound, left hindlimb lame, or right hindlimb lame. For the prospective part, the riding instructors and trainers of varying levels were randomly allocated to three different groups (a, b, c) and given 14 days of feedback-based, computer-aided training in identifying hindlimb lameness, where they assessed 13 videos (of which three were repeated from test 1) of horses trotting in a straight line. Participants in groups a-c received different feedback after each video (group a: correct answer and re-viewing of video at full and 65% speed; group b: correct answer, re-viewing of video at full and 65% speed, narrator providing explanations; group c: correct answer and re-viewing of video at full speed). After computer-aided training, the participants were again subjected to the video test (test 2). Participants also provided background information regarding level of training etcetera. Effects of participants’ background on results were analyzed using analysis of variance, and effects of the different feedback methods were analyzed using generalized estimation equations. On test 1, 44% (group a), 48% (b), 46% (c), and 47% (high-level trainers) of horses were correctly classified. Group a participants significantly improved their test score, both with (p<0.0001) and without (p=0.009) inclusion of repeated videos. For group c, significant improvement was only seen with inclusion of repeated videos (p=0.041). For group b, no significant improvement was seen (p=0.51). Although test 2 scores were low,computer-aided training may be useful for improving hindlimb lameness detection.